Seizure induction by alcohol in patients with epilepsy experience in two hospital clinics. - Heckmatt, J (1990)
We surveyed 70 epileptic patients attending a general neurology clinic and 64 patients attending an epilepsy clinic to determine the incidence of alcohol-related seizures. Seven (10%) of the neurology clinic patients and 9 (15%) of the epilepsy clinic patients reported exacerbation of their seizures with alcohol. In the first group, two had been heavy drinkers when under-age, two had features of alcohol dependence, and three had experienced resolution of seizures following cessation of their drinking. In the second group, five drank 4 units/day or more, and one drank more heavily. The importance of alcohol in the causation of these patients' seizures had not previously been appreciated. The relationship of alcoholism to epilepsy has been recognized for many years, but the role of alcohol in the exacerbation of primary epilepsy, and in triggering seizures in epileptic patients is often not recognized. Control of alcohol ingestion is an important factor in the management of epilepsy.